Little Divergence in America — Market Access and Demographic Transition in the United States - Melanie Guldi; Ahmed S. Rahman (Institute of Labor Economics (IZA), 2022)
This paper assesses the causal impact of greater market access on demographic transition during the latter half of the 19th century in the United States. We construct new measures of fertility changes and measures of railroad access at the county level from 1850 – 1890. We are able to document market-access-induced changes in fertility due to both extensive margins (shifts in occupations with different average fertility rates) and intensive margins (changes in fertility within each occupation class). Both our theoretical model and empirical results suggest that declining fertility in counties mainly occurred through extensive margins. We further discover that fertility changes occurred mainly through strengthening patterns of specialization, rather than through greater industrialization or urbanization, suggesting that demographics diverged within the United States during this period.
Keywords: J11; J13; N11; N31; 330; demographic transition; market access; railroads; fertility; agricultural production; manufacturing production